Percutaneous mechanical circulatory support devices in cardiogenic shock - Mandawat, Aditya (Circ Cardiovasc Interv, 2017)
Despite a high rate of early revascularization and use of intraaortic balloon pump counterpulsation (IABP) therapy, the prognosis of patients with cardiogenic shock (CS) has remained poor. In the hopes of improving outcomes, clinicians are increasing turning to percutaneous left- and right- mechanical circulatory support devices. Until recently, the evidence base for these devices had consisted only of observational data, meta-analyses, and small feasibility trials. In this manuscript, we describe the contemporary outcomes of patients with CS, the hemodynamics of CS, and hemodynamic effects of percutaneous mechanical circulatory support devices. We then use this discussion to provide clinicians with a useful framework for understanding when selecting between or while managing patients with a percutaneous mechanical circulatory support devices. We critically review the recently published data for and against the use of commercially-available devices – the IABP, the Impella system, the TandemHeart, and V-A ECMO - and highlight gaps in our understanding. Given such gaps, a consensus multidisciplinary approach which combines expertise from interventional cardiologists, heart failure specialists, cardiac surgeons, and cardiac anesthesiologists may help pair the right patient with the right device at the right time.